MAFF alleviates hepatic ischemia–reperfusion injury by regulating the CLCF1/STAT3 signaling pathway - Dengliang Lei; Yihua Wang; Shanshan Li; Song Xiang; Yunhai Luo; Ping Yan; Fang Luo; Zuotian Huang; ZhongJun Wu (Cellular & Molecular Biology Letters)
Abstract Background Although hepatic ischemia–reperfusion injury (IRI) frequently occurs during liver resection and transplantation, the underlying mechanisms remain incompletely understood. Through high-throughput sequencing, we found that v-maf musculoaponeurotic fibrosarcoma oncogene homolog F (MAFF) expression was significantly increased after hepatic IRI. The specific role of MAFF, a basic leucine zipper (bZIP) transcription factor, in hepatic IRI is unknown. In the present study, we aimed to explore the effect of MAFF on hepatic IRI injury. Approach and results Adenovirus vectors carrying the MAFF gene were administered to mice to explore the potential significance of MAFF. After ischemia–reperfusion, MAFF expression was significantly upregulated, suggesting a potential association between MAFF expression and hepatocyte apoptosis. A reduction in MAFF expression was demonstrated to worsen hepatic impairment and enhance the expression of proinflammatory cytokines in mice following ischemia–reperfusion. Conversely, MAFF overexpression had the opposite effect. Mechanistically, the combination of CUT&Tag and RNA sequencing technologies identified cardiotrophic factor-like cytokine 1 (CLCF1) as a direct transcriptional target for MAFF and BTB and CNC homology 1 (BACH1) heterodimers. This interaction subsequently triggers signal transducer and activator of transcription 3 (STAT3) signaling. Conclusions MAFF alleviates hepatic ischemia–reperfusion injury by reducing hepatocyte apoptosis and the inflammatory response through the activation of the CLCF1/STAT3 signaling pathway, offering valuable insights into the impact of MAFF on liver protection and potential therapeutic targets for liver treatment. Graphical abstract